2020
DOI: 10.1111/jipb.12994
|View full text |Cite
|
Sign up to set email alerts
|

Betula platyphylla BpHOX2 transcription factor binds to different cis‐acting elements and confers osmotic tolerance

Abstract: The homeodomain-leucine zipper (HD-Zip) proteins play crucial roles in plant developmental and environmental responses. However, how they mediate gene expression to facilitate abiotic stress tolerance remains unknown. In the present study, we characterized BpHOX2 (encoding a HD-Zip I family protein) from birch (Betula platyphylla). BpHOX2 is predominately expressed in mature stems and leaves, but expressed at a low level in apical buds and roots, suggesting that it has tissue-specific characteristics. BpHOX2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Proline is reported to act as both an osmolyte and an ROS scavenger, alleviating damage caused by various stresses [ 50 ]. Overexpression of Betula platyphylla homeodomain-leucine zipper I class homeobox gene ( BpHOX2 ) improved birch plants osmotic tolerance partly by promoting the biosynthesis of proline [ 51 ]. Here, in addition to its function in osmotic adjustment, proline may also have acted as a hydroxy radical scavenger to protect the photosynthetic apparatus under drought in OE lines.…”
Section: Discussionmentioning
confidence: 99%
“…Proline is reported to act as both an osmolyte and an ROS scavenger, alleviating damage caused by various stresses [ 50 ]. Overexpression of Betula platyphylla homeodomain-leucine zipper I class homeobox gene ( BpHOX2 ) improved birch plants osmotic tolerance partly by promoting the biosynthesis of proline [ 51 ]. Here, in addition to its function in osmotic adjustment, proline may also have acted as a hydroxy radical scavenger to protect the photosynthetic apparatus under drought in OE lines.…”
Section: Discussionmentioning
confidence: 99%
“…Each sample contained at least 9 seedlings, and three independent experiments were performed. qRT-PCR was used to detect the relative expression levels of five ABA biosynthesis-related genes (NCED1, 3, 4, ZEP, and AAO3) (Tan et al, 2020) in OE transgenic plants after normal condition and stress with 150 mM NaCl for 24 h. The primers used for qRT-PCR are listed in Supplementary Table 1.…”
Section: Biochemical Staining and Physiological Measurements Of Transformed Plantsmentioning
confidence: 99%
“…ROS accumulation depends largely on the balance between ROS production and simultaneous ROS scavenging (Liu et al, 2019 SOD and POD play a central part (Wei et al, 2019). Previous studies have shown that expression of BpHOX2 (which encodes an HD-Zip I family protein) increased POD and SOD activities to scavenge excess ROS, ultimately reducing ROS levels and enhancing osmotic stress tolerance (Tan et al, 2020). In this work, POD and SOD enzyme activities under salt stress were significantly higher in MdHB7-like OE lines and lower in RNAi lines compared with GL-3 plants (Figure 6).…”
Section: Discussionmentioning
confidence: 99%